2009
DOI: 10.2741/3305
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage antioxidant protection within atherosclerotic plaques

Abstract: Macrophage cells within inflammatory lesions are exposed to a wide range of degrading and cytotoxic molecules including reactive oxygen species. Unlike neutrophils, macrophages do not normally die in this environment but continue to generate oxidants, phagocytose cellular remains, and release a range of cyto-active agents which modulate the immune response. It is this potential of the macrophage cell to survive in an oxidative environment that allows the growth and complexity of advanced atherosclerotic plaque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 114 publications
0
18
0
1
Order By: Relevance
“…A correlate to support this idea is seen in studies of the inflammatory and oxidative cascades produced by coronary plaques causing myocardial infarction, with extent of oxidative stress shown to correlate with severity of atherosclerosis in the coronary arteries. [26, 27] Additionally, evidence exists that tumor necrosis factor-α, a known key inflammatory mediator, significantly modulates the risk for aneurysm formation and aSAH[28]…”
Section: Discussionmentioning
confidence: 99%
“…A correlate to support this idea is seen in studies of the inflammatory and oxidative cascades produced by coronary plaques causing myocardial infarction, with extent of oxidative stress shown to correlate with severity of atherosclerosis in the coronary arteries. [26, 27] Additionally, evidence exists that tumor necrosis factor-α, a known key inflammatory mediator, significantly modulates the risk for aneurysm formation and aSAH[28]…”
Section: Discussionmentioning
confidence: 99%
“…For clarity, not all the cell preparations' HOCl viability curves have been shown in (A). 7,8-dihydroneopterin to protect cells has not been demonstrated (Gieseg et al, , 2009). …”
Section: Discussionmentioning
confidence: 96%
“…Here we have shown that when 7,8-dihydroneopterin is added extracellularly, it can also outcompete the intracellular GSH even at high HOCl concentrations. 7,8-Dihydroneopterin is generated at micromolar concentrations in sites of inflammation by interferon stimulated macrophages (Firth et al, 2008;Gieseg et al, 2009). Unfortunately attempts to reproduce these 7,8-dihydroneopterin concentrations in tissue culture with stimulated cells have to date been unsuccessful, so the potential of de novo synthesized Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…HOCl reacts extremely rapidly with 7,8-dihydroneopterin to generate neopterin [20,21], suggesting that a significant amount of the neopterin measured in serum and urine may be from the scavenging of HOCl released by neutrophils and macrophages during inflammation. These in vitro studies have led to the proposal that 7,8-dihydroneopterin is generated by macrophages to protect these cells from oxidants generated during inflammation [6,13,22,23].…”
Section: Introductionmentioning
confidence: 99%